Evolusi Kepemimpinan Digital: Transformasi Modal Manusia dalam Era Artificial Intelligence - Choirul Anam; Dian Candra Dewi; Ahmad Fairuzabadi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The technological revolution accelerated by Artificial Intelligence (AI) has fundamentally changed the paradigm of leadership and human resource management. Digital leadership is now an essential competency for organizations that want to survive and thrive in the face of the challenges of the technological disruption era. This research aims to understand the role of digital leadership in the human capital transformation process, especially in the context of AI adoption by modern organizations.The post-qualitative approach allows research to capture the evolving and diverse dynamics in a digitized organizational environment. It is more open to different forms of data, both structured and unstructured, and recognizes the complexity and ambiguity in digital leadership practices. This research utilizes open-ended interviews and participatory observation, facilitated by interpretive narrative to understand the process of human capital transformation. The main results of the study show that digital leadership plays a key role in facilitating human capital transformation, with an emphasis on adaptive skills development, data-driven decision-making and closer collaboration between people and technology. This transformation is not only technical in nature but also involves changes in organizational culture and structure. This research makes an important contribution by offering a new perspective in leadership studies through a post-qualitative approach.